2023
DOI: 10.1186/s12575-023-00194-2
|View full text |Cite
|
Sign up to set email alerts
|

A 3D human co-culture to model neuron-astrocyte interactions in tauopathies

Abstract: Background Intraneuronal tau aggregation is the major pathological hallmark of neurodegenerative tauopathies. It is now generally acknowledged that tau aggregation also affects astrocytes in a cell non-autonomous manner. However, mechanisms involved are unclear, partly because of the lack of models that reflect the situation in the human tauopathy brain. To accurately model neuron-astrocyte interaction in tauopathies, there is a need for a model that contains both human neurons and human astroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…These data, as well the data presented in our primary research paper (Batenburg et al., 2022), demonstrate the feasibility of FTDtau 1+2 to model tau aggregation without the use of seeds that have thus far been a requirement for the induction of tau aggregation in human iPSC‐derived neurons (Verheyen et al., 2015). In addition, we have showed that expression of FTDtau 1+2 induces tau aggregation in a three‐dimensional neuron/astrocyte co‐culture (Batenburg et al., 2023), highlighting the versatility of this approach to induce spontaneous tau aggregation in more advanced cell culture models. Although seeds may be heterogeneous and directly affect neurons and astrocytes independent of intraneuronal tau pathology, their use represents an established paradigm in cellular models and may be of interest for specific research questions.…”
Section: Commentarymentioning
confidence: 96%
See 4 more Smart Citations
“…These data, as well the data presented in our primary research paper (Batenburg et al., 2022), demonstrate the feasibility of FTDtau 1+2 to model tau aggregation without the use of seeds that have thus far been a requirement for the induction of tau aggregation in human iPSC‐derived neurons (Verheyen et al., 2015). In addition, we have showed that expression of FTDtau 1+2 induces tau aggregation in a three‐dimensional neuron/astrocyte co‐culture (Batenburg et al., 2023), highlighting the versatility of this approach to induce spontaneous tau aggregation in more advanced cell culture models. Although seeds may be heterogeneous and directly affect neurons and astrocytes independent of intraneuronal tau pathology, their use represents an established paradigm in cellular models and may be of interest for specific research questions.…”
Section: Commentarymentioning
confidence: 96%
“…Human iPSCs should harbor a stably integrated doxycycline-inducible rtTA/Ngn2 transgene cassette. We used a previously generated clonal human iPSC line stably expressing rtTA/Ngn2 (Frega et al, 2017) that was maintained as previously described (Batenburg et al, 2022(Batenburg et al, , 2023. For culture procedures for human iPSCs, see Support Protocol 1.…”
Section: Start Neuronal Induction Of Ngn2-ipscs (Day -2)mentioning
confidence: 99%
See 3 more Smart Citations